2019
DOI: 10.36251/josi.160
|View full text |Cite
|
Sign up to set email alerts
|

Insights into theorizing social exclusion and inequities: A perspective from the Arab World

Abstract: Objective: To explore the influence of the global structural determinants and their pathways of action on health disparities and social exclusion, drawing on findings from research with four different population groups in an Arab context. We use a socioecological framework to categorise these determinants into levels to allow an in-depth look into their pathways of action on social exclusion and inequalities. Methods: We use findings from an ethnographic study on Palestinian and Iraqi refugees in Lebanon; a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The fear from medical procedures and from being subject to sub-standard care expressed in women’s narratives reflects the lack of accountability in the Lebanese healthcare system [ 48 ] especially when they consider they are reliant on humanitarian aid to receive healthcare because they are refugees. These systems continue to alienate and silence women, deprive them of their right to information, segregate them as refugees and isolate them from their support systems [ 49 ]. Similarly, women’s choices of their healthcare providers, type of birth and anesthetic are limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fear from medical procedures and from being subject to sub-standard care expressed in women’s narratives reflects the lack of accountability in the Lebanese healthcare system [ 48 ] especially when they consider they are reliant on humanitarian aid to receive healthcare because they are refugees. These systems continue to alienate and silence women, deprive them of their right to information, segregate them as refugees and isolate them from their support systems [ 49 ]. Similarly, women’s choices of their healthcare providers, type of birth and anesthetic are limited.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of women’s reports on obstetric violence in the Eastern Mediterranean region indicates that disrespect and abuse during childbirth is reported by women from all countries of the region and that socio-cultural norms related to patriarchy and the professional dominance of healthcare providers normalize these behaviors with the healthcare system [ 35 ]. Our previous work in Lebanon and Arab countries has shown that women are silenced and marginalized in the healthcare system during childbirth [ 36 ]. Given this background, we aim at understanding women’s interpretation of the meaning and experiences of “respect” and “disrespect”.…”
Section: Introductionmentioning
confidence: 99%
“…This interest in the practice of research ethics has particularly arisen due to sensitive issues, widespread vulnerability and marginalization among the region's populations (19). The MENA region has historically witnessed social turmoil, wars, impoverishment, economic recessions, and deeply rooted social injustices which continue to have adverse impacts on people's health (20). Consequently, the number of publications on war-affected populations in the region has ensued since the start of the 21st century and extending to the study of the civil uprisings in 2011 (21) and during the COVID-19 pandemic when a substantial increase in COVID-19 related research has taken place in Saudi Arabia, funded by local and international agencies (22).…”
Section: The Mena Contextmentioning
confidence: 99%